2022
DOI: 10.1007/s00436-022-07459-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular identification of zoonotic Anisakis and Pseudoterranova species in fish destined to human consumption in Chile

Abstract: Zoonotic larvae of the family Anisakidae found in several fish species represent a serious risk in public health since they may cause food-borne anisakidosis in humans. Chile has culinary preferences including eating raw fish in many traditional preparations. In the present study, a total of 180 fish specimens representing three different fish species, i.e., Chilean hake (Merluccius gayi), snoek (Thyrsites atun), and sea bream (Brama australis), were caught at central coast of Chile. Parasitological examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A recent study examining ready-to-eat mackerel (Scomber japonicus) samples in Japan found that 54% (244/448) were infected with Anisakis nematode (Ohnishi et al, 2023). In Chile, a survey indicated that almost all Chilean hake (Merluccius gayi) and sea bream (Brama australis) were parasitized with Anisakis (Muñoz-Caro et al, 2022). Another survey in Portugal on European hake (M. merluccius) showed that Anisakis had a prevalence of 76.7% (Santos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examining ready-to-eat mackerel (Scomber japonicus) samples in Japan found that 54% (244/448) were infected with Anisakis nematode (Ohnishi et al, 2023). In Chile, a survey indicated that almost all Chilean hake (Merluccius gayi) and sea bream (Brama australis) were parasitized with Anisakis (Muñoz-Caro et al, 2022). Another survey in Portugal on European hake (M. merluccius) showed that Anisakis had a prevalence of 76.7% (Santos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We observed a distribution of Pseudoterranova bulbosa in different microhabitats, liver and viscera, within the body cavity of Atlantic Cod ( Gadus morhua ) caught off Greenland. Since aggregations of anisakid larvae have often been observed in the liver of fish hosts (Klapper et al., 2018; Muñoz‐Caro et al., 2022; Nadolna & Podolska, 2014; Najda et al., 2018; Severin et al., 2020), we hypothesized that this effect could become visible in a differential gene expression analysis, giving insight into the activities (e.g., feeding on blood or tissue in the liver) of anisakid L3 within their paratenic fish host.…”
Section: Introductionmentioning
confidence: 99%